Magnetotransport and internodal tunnelling in Weyl semimetals - G. Bednik; K. S. Tikhonov; S. V. Syzranov (Physical Review Research, 2020)
Internodal dynamics of quasiparticles in Weyl semimetals manifest themselves in hydrodynamic, transport, and thermodynamic phenomena and are essential for potential valleytronic applications of these systems. In an external magnetic field, coherent quasiparticle tunnelling between the nodes modifies the quasiparticle dispersion and, in particular, opens gaps in the dispersion of quasiparticles at the zeroth Landau level. We study magnetotransport in a Weyl semimetal taking into account mechanisms of quasiparticle scattering, both affected by such gaps and independent of them. We compute the longitudinal resistivity of a disordered Weyl semimetal with two nodes in a strong magnetic field microscopically and demonstrate that in a broad range of magnetic fields, it has a strong angular dependence, ρ(η)∝C_{1}+C_{2}cos^{2}η, where η is the angle between the field and the separation between the nodes in momentum space. The first term is determined by the coherent internodal tunnelling and is important only at angles η close to π/2. This contribution depends exponentially on the magnetic field, ∝exp(−B_{0}/B). The second term is weakly dependent on the absolute value of the magnetic field for realistic concentrations of the impurities in a broad interval of fields.